Effectiveness Of a Psychoeducational Program for The Development of Social Skills in Children - Estrada-Araoz, Edwin Gustavo; Larico-Uchamaco, Guido Raúl; Huamaní-Pérez, María Isabel; Huamani-Calloapaza, Tatiana Carmen; Barrionuevo-Alosilla, Pamela (Journal of Ecohumanism, 2024)
Social skills play a fundamental role in the integral development of children, influencing their emotional well-being and future interpersonal relationships. Therefore, the objective of this research was to evaluate the effectiveness of a psychoeducational program in the development of social skills in primary education students. The research approach was quantitative, the design was experimental and the type was pre-experimental. The sample was made of 35 students of the fifth grade of primary education from a state educational institution in the city of Puerto Maldonado (Peru). A psychoeducational program of social skills was applied during 15 sessions and to evaluate its effectiveness, a questionnaire was administered before and after the intervention, which had adequate psychometric properties. The results indicate that there are statistically significant differences (p<0.05) between the general scores of the average before (138.69) and then (158.94) of the application of the psychoeducational program. Regarding the scores of the dimensions, statistically significant differences were also reported between the scores of the average before and after (p<0.05). It was concluded that the application of the psychoeducational program was effective in the development of the social skills of primary education students.